1997
DOI: 10.1097/00002030-199704000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Saquinavir pharmacokinetics alone and in combination with ritonavir in HIV-infected patients

Abstract: For some patients, administration of SQV 600 mg three times daily results in very low SQV plasma levels and possibly little antiviral effect. Combination of SQV with RIT results in a significant drug interaction mediated by enzyme inhibition which exposes patients to very high SQV concentrations and potential toxicity. If combination therapy with SQV plus RIT is considered then the dose of SQV should be greatly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
104
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(109 citation statements)
references
References 10 publications
5
104
0
Order By: Relevance
“…Initial pharmacokinetic studies showed that upon pretreatment of rats with RTV, the AUC 0 -10h of DPC showed 2.5-fold enhancement. RTV is known to cause such effects by potent inhibition of the metabolizing isozyme CYP3A Merry et al, 1997;Koudriakova et al, 1998) and the transporter Pgp (Alsenz et al, 1998). DPC is indeed metabolized prominently by CYP3A4, like most other HIV protease inhibitors, and is also shown to be a good substrate for Pgp, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Initial pharmacokinetic studies showed that upon pretreatment of rats with RTV, the AUC 0 -10h of DPC showed 2.5-fold enhancement. RTV is known to cause such effects by potent inhibition of the metabolizing isozyme CYP3A Merry et al, 1997;Koudriakova et al, 1998) and the transporter Pgp (Alsenz et al, 1998). DPC is indeed metabolized prominently by CYP3A4, like most other HIV protease inhibitors, and is also shown to be a good substrate for Pgp, as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…Ritonavir is a potent inhibitor of CYP3A4 and coadministration of RTV and SQV results in increases in the C max and AUC of SQV [205,206]. The AUCs of the hard and soft gel formulations of SQV have been shown to increase in the presence of RTV .50-fold and 20-fold respectively [206,207].…”
Section: Saquinavir (Sqv)mentioning
confidence: 99%
“…The AUCs of the hard and soft gel formulations of SQV have been shown to increase in the presence of RTV .50-fold and 20-fold respectively [206,207]. Similarly, the protease inhibitors nel®navir and indinavir inhibit CYP3A4, increasing mean plasma concentrations and AUCs of SQV during co-administration.…”
Section: Saquinavir (Sqv)mentioning
confidence: 99%
See 2 more Smart Citations